Design of MABBAR (Mari Belajar Bahasa Arab): A Web-Based Evaluation System for Enhancing Arabic Listening Competency (Mahārah al-Istimā’) in Junior High Schools - fatchiatuzahro fatchiatuzahro; Muhammad Ainul Haq; Ubay Abdillah; Friendis Syani Amrullah; Abdul Fatah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2026)
الملخص إن محدودية البيئة اللغوية وطرق التقويم التقليدية غالباً ما تعيق تطوير مهارة الاستماع لدى طلاب المرحلة المتوسطة. تهدف هذه الدراسة إلى تطوير نظام